Hubungan Unsur Manajemen Dengan Penerapan Sistem Informasi Manajemen Puskesmas di Kabupaten Boyolali - Susilo, Didik Agus; , Sri Sugiarsi, SKM, M.Kes; , Arief Kurniawan NP, SKM, M.PH (2015)
District Health Offices of Boyolali Regency has reactivated health information system in community health center (SIMPUS) in 2015. To implementation the system, required tool of management to perform its functions. The purpose of this research is to perceive the correlation tool of management (man, money, material, machine and method) with the implementation of SIMPUS.This research is observational analytical used quantitative methods to analyse correlation between tool of management with SIMPUS implementation in Boyolali community health center. Research population are users of SIMPUS at community health center have implemented SIMPUS (15 community health center) all have 33 person. The sample in this research are 30 respondents used proportional random sampling method. The analysis ere descriptive analysis and analytic analysis using spearman rank correlation.The results of the rank spearman analysis shows there has a correlation between the tool of man, material, machine and method with implementation of SIMPUS. But there hasn't correlation between the tool of money with the implementation of SIMPUS